USER COLOR PREFERENCES IN DAILY USE PRODUCTS - ÜNAL, Bülent (Atlas Journal, 2021)
Color plays an important role in creating a certain factor of preference and it is identified as an important design tool for many products, as consumers will often choose to buy a product when it is presented in preferred colors or color schemes. In this study it was decided to investigate the effect of the color as a design element for preference in daily use products and which color has the potential to be preferred more than others. In addition, it was aimed to analyze the effect of gender on color preferences and on the factors that influence color preferences. As a result of the study, it was reported that red and gray colors were preferred more than green and blue colors; and a significant difference between gender groups in their color choices were found. Considering the gender differences, it was seen that there is a relationship between the mentioned factors and genders. The study suggests that offering a choice of product colors to consumers may be advantageous in the field of products for daily use as it has a potential to provide an attractive method to convey messages about product features and influence consumer choice decisions that affect their purchase.